2011
DOI: 10.1093/pasj/63.sp3.s963
|View full text |Cite
|
Sign up to set email alerts
|

Suzaku and XMM-Newton Observations of the Fornax Cluster: Temperature and Metallicity Distribution

Abstract: Suzaku observed a central region and five offset regions within 0.2 $\ r_{180}$ in the Fornax cluster, a nearby poor cluster, and XMM-Newton mapped the cluster with 15 pointings out to 0.3 $\ r_{180}$ . The distributions of O, Mg, Si, S, and Fe in the intracluster medium (ICM) were studied with Suzaku, and those of Fe and temperature were studied with XMM. The temperature of the ICM gradually decreases with the radius from 1.3 keV at 0.04 $\ r_{180}$ to 1 keV at 0.2–0.3 $\ r_{180}$ . If the new solar abundance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 55 publications
6
27
0
Order By: Relevance
“…The projected abundance values from S09 are somewhat higher than that from Rasmussen and Ponman (2009) at r > 0.3r 500 . The S09 results are consistent with the results of Johnson et al (2009) (a sample of 28 groups with a median temperature of 1.04 keV from the XMM-Newton data) and are also consistent with the Suzaku results for five ∼1 keV groups (a median iron abundance of ∼0.2 at r ∼ 0.35r 500 (Murakami et al 2011); note the different solar abundance tables used in different works). Buote et al (2004) also reported a low iron abundance (∼0.1 solar) in a southern portion of the (0.3-0.6) r 500 sector for NGC 5044, but the iron abundance in another direction of the (0.3-0.45) r 500 sector from the Suzaku data is twice higher (Komiyama et al 2009).…”
Section: Are the Hot Gas In Galaxy Groups Metal-poor?supporting
confidence: 90%
See 1 more Smart Citation
“…The projected abundance values from S09 are somewhat higher than that from Rasmussen and Ponman (2009) at r > 0.3r 500 . The S09 results are consistent with the results of Johnson et al (2009) (a sample of 28 groups with a median temperature of 1.04 keV from the XMM-Newton data) and are also consistent with the Suzaku results for five ∼1 keV groups (a median iron abundance of ∼0.2 at r ∼ 0.35r 500 (Murakami et al 2011); note the different solar abundance tables used in different works). Buote et al (2004) also reported a low iron abundance (∼0.1 solar) in a southern portion of the (0.3-0.6) r 500 sector for NGC 5044, but the iron abundance in another direction of the (0.3-0.45) r 500 sector from the Suzaku data is twice higher (Komiyama et al 2009).…”
Section: Are the Hot Gas In Galaxy Groups Metal-poor?supporting
confidence: 90%
“…Rasmussen and Ponman (2009) derived a rising Si/Fe profile at r > 0.3r 500 , whereas the Suzaku results are consistent with a flat α/Fe ratio profile at r ∼ 0.5 r 500 for Si, O, S and Mg (e.g. Sato et al 2010, Murakami et al 2011.…”
Section: Are the Hot Gas In Galaxy Groups Metal-poor?mentioning
confidence: 69%
“…Furthermore, FCC 219 is known to host a substantial hot-gas halo (e.g. Machacek et al 2005), whereas FCC 167 shows a much weaker X-ray halo in the deep XMM-Newton images from Murakami et al (2011) and Su et al (2017). This difference is relevant to the discussion of our PNe results for these two objects.…”
Section: Introductionmentioning
confidence: 82%
“…One potential source of this difference might be the hot gas halo in FCC 219, as demonstrated by X-ray data (e.g. Jones et al 1997;Murakami et al 2011). However, FCC 167 does not posses as significant a hot-gas interstellar or inter-galactic medium component.…”
Section: Luminosity-specific Pn Frequencymentioning
confidence: 99%
“…The column density is fixed at the Galactic value, however post facto fits with the higher absorption determined from the innermost annulus (see below) yield virtually identical results. The background-component temperatures in the spectra extracted from other regions are fixed at these outer region best-fit values: kT (LHB) = 0.105, kT (MWH) = 0.187, kT (ICM) = 1.69, as is the MWH/LHB flux ratio (Murakami et al 2011). Relaxing these constraints did not significantly impact the best-fit ISM parameters.…”
Section: Suzaku Spectral Analysismentioning
confidence: 99%